THE INFLUENCE OF TRUST, EASE OF USE, AND ONLINE CONSUMER REVIEW ON CONSUMER PURCHASE DECISIONS (Study on TikTok Shop Users in Rembang City) - Devi Puspitasari; Suzy Widyasari (Jurnal Ekonomi, 2023)
This study aims to test and analyze the influence of trust, ease of use, and online consumer reviews on purchasing decisions. The objects in this research are the consumers of the TikTok Shop in the city of Rembang. This research is a quantitative research that implements a purposive sampling method with a sample size of 100 respondents, obtained through the distribution of Google from. Scale measurements carried out by researchers using a 5-point Likert scale with the data testing method. Testing the data used is the instrument test, including validity testing and reliability testing (multiple linear regression analysis and model testing (coefficient of determination, F test, and t test)) which are processed with SPSS version 23. Based on the results of this study, it is drawn The conclusion is that trust, ease of use, and online consumer reviews have positive and significant influence on purchasing decisions.